Thermodynamics and kinetics of hydrogen/deuterium absorption–desorption in Pd0.77Ag0.23 alloy. (5th January 2015) - Anand, N.S.; Pati, Subhasis; Jat, Ram Avtar; Parida, S.C.; Mukerjee, S.K.
Abstract: Pd0.77 Ag0.23 alloy foil of thickness ∼100 μm was prepared by arc melting followed by cold rolling and annealing. The X-ray diffraction pattern confirmed the formation of solid solution phase and the TXRF analysis confirmed the composition as Pd0.77 Ag0.23 . Hydrogen/deuterium equilibrium pressure-composition-temperature (PCT) relationships for this alloy were experimentally generated over the temperature range of 374–419 K using Sieverts' type volumetric apparatus. Thermodynamic parameters like enthalpy and entropy of hydrogen/deuterium desorption reaction were evaluated from PCT data. Kinetics of hydrogen/deuterium absorption for this thin alloy foil was also investigated in the temperature range of 335–394 K using the same apparatus and activation energies of hydrogen/deuterium absorption reactions were evaluated. Both thermodynamic and kinetic data showed pronounced positive isotope effect in the temperature and pressure range of investigation. Highlights: Generation of pressure-composition-temperature (PCT) profiles for Pd0.77 Ag0.23 –H2 /D2 systems. Constant volume kinetic measurements of hydrogen/deuterium absorption by Pd0.77 Ag0.23 alloy foil. Generation of thermodynamic and kinetic parameters for Pd0.77 Ag0.23 –H2 /D2 systems. Hydrogen isotope effect on the thermodynamic and kinetic parameters.